Perkembangan Kegiatan Pottery Class Sebagai Wisata Minat Khusus Di Ubud, Gianyar, Bali - Zetti, Azra; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p24, 2024)
Bali, as one of the most popular tourist destinations, offers a wide array of activities and attractions that cater to travelers' preferences. Pottery classes have emerged as a particularly sought-after niche activity among tourists. The tourism potential in the Ubud region of Bali is notable for its variety of specialized interest activities such as craft classes. As specialized interest tourism evolves, efforts are needed to ensure its sustainability, including understanding tourists' interests in these activities, especially pottery classes in Ubud. This research aims to explore tourists' interest in participating in pottery class tourism activities and to identify the development of pottery classes as a specialized interest tourism attraction in Ubud, Gianyar. Utilizing qualitative methodology, the study employs observation, semi-structured interviews, and literature review to collect data. The findings reveal that tourists interested in ceramic craft activities are often drawn by their passion for arts, particularly ceramics, and view such activities as opportunities to unwind from daily pressures. The growing interest among tourists in pottery classes has contributed significantly to the development of these activities, particularly in Ubud, Gianyar. The high demand for pottery classes has led to numerous businesses offering such activities, underscoring the need to monitor their development to ensure sustained growth. This not only supports the local economy in Ubud, Gianyar but also enhances the tourism experience by promoting cultural engagement and creative pursuits. Understanding and fostering the growth of pottery classes in Ubud, Gianyar is crucial for their continued success as sustainable tourism activities that contribute positively to the local community. Keywords: Development of Pottery Class in Ubud, Special Interest Tourism, Tourist Interests